Scientific Update on the Pharmacognostic, Pharmacological and Phytochemical Properties of Thevetia peruviana - Gaur, Rishabh; Rathore, Anamika; Sharma, Anuj Kumar; Pathak, Devender; Kulshreshtha, Mayank (Pharmacognosy Communications)
The human race has embraced technology to a great extent in the modern world of living things. Although advanced technologies are great, they also produce a great deal of disease in the human health care system, where India has achieved ranking of 4th, 5th, and even 2nd in the globe. The purpose of this review is to condense the existing scientific and molecular information about Thevetia peruviana, including its pharmacognostic characteristics, pharmacological potential, phytochemical qualities, and potential future research areas. Using Google, PubMed, Scholar, and other web resources, data were gathered.
Keywords: Thevetia peruviana; Pharmacognosy; Pharmacology; India; Future scope